Effects of groove constraint space on plasma characteristics during Laser-MIG hybrid welding of Titanium alloy. (December 2019) - Huang, Anguo; Zhang, Jiajia; Gao, Chuang; Hu, Renzhi; Pang, Shengyong
Abstract: Laser-MIG hybrid welding with groove shows great potential in thick plate joining. However, the plasma behaviors influenced by the groove space are not well understood. In this paper, special stair-stepping plates with groove were designed to form different groove configurations, and the effects of groove depth on the plasma characteristics were investigated systematically. The results showed that the plasma temperature decreased from 10, 589 K to 8, 527 K and the electron density increased from 1.30 × 10 16 cm −3 to 1.44 × 10 16 cm −3, when the groove depth increased from 0 to 20 mm. The reason may be that more laser-induced metal vapor, cooler than arc plasma, cannot leave the deeper groove space in time. The heat convection and radiation between the vapor and plasma resulted in the temperature decrease. Besides, as the groove constraint space increased, the plasma profile, frequency of droplet-transfer and weld width decreased, while the penetration depth increased to some extent. This research results would be inspirational and meaningful to the laser-arc hybrid welding of medium and thick plate.